Engaging reality: examining how location-aware mixed reality mobile apps and games influence sense of place for a more engaged citizenry - Bamesberger, Carla, author (Colorado State University. Libraries, 2019)
Growing concerns regarding declining community and civic engagement as a result of increased access to new technologies calls for research seeking to understand ways that purposeful design could have a reverse impact. Location-aware mixed reality mobile apps may be one such technology that, with purposeful design, have the potential to engage users in their communities. Examining these technologies in the context of sense of place theory will provide insights to how these technologies may impact user engagement in their community. Sense of place theory posits that individuals' experiences in a place contribute to their sense of what that place is like and increase their sense of place. An increased sense of place increases a person's likelihood of becoming engaged in that place and of taking an active role in preserving or improving that place. This exploratory study considers the potential of location-aware mixed reality mobile apps to positively impact users' sense of place, making them more likely to engage in and participate in their community. Twelve users (four for each of the three mixed reality apps under consideration) were interviewed about their experience of place while using the app. Interview transcripts were coded and analyzed for sense of place topics.
27 - Carla Bamesberger
Examining how mixed reality mobile apps enhance sense of place
Public Communication and Technology.
Keywords: augmented reality; location-aware mixed reality; mobile app; sense of place; mixed reality